ChemInform Abstract: Pd(0)‐Catalyzed Decarboxylative Coupling and Tandem C—H Arylation/Decarboxylation for the Synthesis of Heteroaromatic Biaryls. Issue 7 (22nd February 2013) - Nandi, Debkumar; Jhou, Yang‐Ming; Lee, Jhen‐Yi; Kuo, Bing‐Chiuan; Liu, Chien‐Yu; Huang, Pei‐Wen; Lee, Hon Man
Abstract In the presence of carbene complex PAL, the acids (I) and (IV) undergo decarboxylative coupling with aryl bromides as a new and regioselective access to heteroaromatic biaryls like (III) and (V).